2013
DOI: 10.5194/acp-13-5731-2013
|View full text |Cite
|
Sign up to set email alerts
|

Diel peroxy radicals in a semi-industrial coastal area: nighttime formation of free radicals

Abstract: Peroxy radicals were measured by a PeRCA (Peroxy Radical Chemical Amplifier) instrument in the boundary layer during the DOMINO (Diel Oxidant Mechanisms In relation to Nitrogen Oxides) campaign at a coastal, forested site influenced by urban-industrial emissions in southern Spain in late autumn. Total peroxy radicals (RO2* = HO2 + ΣRO2) generally showed a daylight maximum between 10 and 50 pptv at 13:00 UTC, with an average of 18 pptv over the 15 days of measurements. Emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Methylglyoxal is formed at high yield from the OHinitiated oxidation of several biogenic (especially isoprene) and anthropogenic VOCs, e.g. via degradation of aromatic hydrocarbons (Arey et al, 2009;Obermeyer et al, 2009) and is found in biomass-burning-impacted air masses (Fu et al, 2008;Akagi et al, 2011;Stockwell et al, 2015) and those influenced by urban emissions of aromatics (Liu et al, 2010). It is also formed at yields of several percent from the ozonolysis of monoterpenes such as α-Pinene and 3 -carene (Yu et al, 1998;Fick et al, 2003), which were both present at high concentrations during HUMPPA-COPEC-2010.…”
Section: Box Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylglyoxal is formed at high yield from the OHinitiated oxidation of several biogenic (especially isoprene) and anthropogenic VOCs, e.g. via degradation of aromatic hydrocarbons (Arey et al, 2009;Obermeyer et al, 2009) and is found in biomass-burning-impacted air masses (Fu et al, 2008;Akagi et al, 2011;Stockwell et al, 2015) and those influenced by urban emissions of aromatics (Liu et al, 2010). It is also formed at yields of several percent from the ozonolysis of monoterpenes such as α-Pinene and 3 -carene (Yu et al, 1998;Fick et al, 2003), which were both present at high concentrations during HUMPPA-COPEC-2010.…”
Section: Box Model Resultsmentioning
confidence: 99%
“…Biacetyl is formed in the photo-oxidation of aromatic hydrocarbons in the presence of NO x (Atkinson et al, 1980;Arey et al, 2009;Obermeyer et al, 2009) and is also expected to be present in biomass-burning-impacted air masses. The proposed intermediacy of dicarbonyls such as methylglyoxal and biacetyl in forming PAA in this study is consistent with the dominant role for di-and trialkyl benzenes in PAA formation found by Zhang et al (2010).…”
Section: Box Model Resultsmentioning
confidence: 99%
“…Nighttime peroxy radicals are low but consistently above the PeRCIMS detection limit of 2 pptv, with mean mixing ratios from 00:00 to 05:00 of 4 ± 2 pptv and 6 ± 2 pptv for HO * 2 and HO 2 + RO 2 , respectively. Observations in at least one semipolluted area have suggested that NO 3 (nitrate radical) and/or ozone-driven chemistry can drive significant nighttime peroxy radical production in the presence of alkenes (Andres-Hernandez et al, 2013). For the conditions of BEA-CHON, Fry et al (2013) have demonstrated that the oxidation of monoterpenes by NO 3 chemistry can be a significant source of particulate organic nitrates.…”
Section: Observationsmentioning
confidence: 99%
“…Missing night-time reactivity attributed to unmeasured secondary organic compounds. Lou et al (2010); Lu et al (2012Lu et al ( , 2013 Andrés- Hernández et al (2013) HO x concentrations in polluted or semi-polluted environments. Highlights from these studies are discussed here, with particular attention paid to those involving measurements of HO x , NO 3 , and O 3 and to those in which the contributions made by O 3 and NO 3 to night-time radical chemistry have been considered.…”
Section: H M Walker Et Al: Night-time Measurements Of Ho Xmentioning
confidence: 99%